Acoustic evidence for topographic blocking on a steep submarine canyon wall - Astrid B. Leitner; Chad M. Waluk; Kim R. Reisenbichler; Rob E. Sherlock; Bruce H. Robison; Kelly J. Benoit‐Bird (Limnology and Oceanography, 2026)
Diel vertical migration (DVM) is the largest mass‐movement of animals on Earth, with profound ecological and biogeochemical consequences. DVM has mostly been studied in the open ocean; however, at steep slopes, pelagic animals including vertical migrators must contend with the seafloor, emphasizing the importance of understanding DVM in these prevalent, critical habitats. Here we used active acoustics in combination with video to conduct a detailed study of the interactions of vertical migrators with the steep wall of a submarine canyon during their sunrise descent. We found regular and frequent, high‐density sunrise aggregations of animals consistent with seafloor blocking of descending vertical migrators across all seasons. While topographic blocking was thought to be primarily caused by nighttime advection of migrators over shallows by prevailing currents, here the occurrence of this phenomenon was observed to be largely independent of oceanographic drivers including advection as measured by an ADCP, providing evidence that behavior plays an important role. Advection, season, upwelling, and other environmental factors were found to impact specific characteristics of sunrise aggregations but not likelihood of occurrence. Given its intensity and prevalence, topographic blocking likely creates high‐quality, predictable foraging opportunities for a large diversity of predators and influences the abundance and habitat use of predators in the area. The steep slopes of this canyon, as with any abrupt bathymetry, juxtapose the deep and the shallow, the benthic and the pelagic, and the offshore and nearshore. Thus, topographic blocking may be prevalent in other steep canyons and at steep bathymetry more generally.

Running the Gauntlet: Assessing the Threats to Vertical Migrators - Bruce H. Robison; Rob E. Sherlock; Kim R. Reisenbichler; Paul R. McGill (Frontiers in Marine Science, 2020)

“Little Red Jellies” in Monterey Bay, California (Cnidaria: Hydrozoa: Trachymedusae: Rhopalonematidae) - George I. Matsumoto; Bastian Bentlage; Rob Sherlock; Kristine Walz; Bruce H. Robison (Frontiers in Marine Science, 2020)

The Coevolution of Midwater Research and ROV Technology at MBARI - Bruce Robison; Kim Reisenbichler; Rob Sherlock (Oceanography, 2017)

Nitrous oxide emissions from grazed grassland as affected by a nitrification inhibitor, dicyandiamide, and relationships with ammonia-oxidizing bacteria and archaea - Hong J. Di; Keith C. Cameron; Rob R. Sherlock; Ju-Pei Shen; Ji-Zheng He; Chis S. Winefield (Journal of Soils and Sediments, 2010)